ENERGY ACTIVATION OF DECOMPOSITION OF CASTINGS OF PURE ALUMINUM-STANNUM ALLOY - Aldika Aldika; Nukman Nukman (Asosiasi Peneliti Sriwijaya, 2022)
Thermogravimetry analyser is a tool to perform thermal analysis where the mass of the test material will be inversely or directly proportional to the increasing temperature rate and a function of time (constantly increasing temperature). The results of the TGA test are a comparison of mass to times, mass to DTA, and the ln k to 1/t; all relations to determine the oxidation point and activation energy required for each sample can be known. The samples used were 4: pure aluminium, pure aluminium mixed with 2% Sn, pure aluminium mixed with 6% Sn, and pure aluminium mixed with 10% Sn. The activation energy required for each sample is as follows, pure Aluminium of 64.24 kJ/mol, pure Aluminium mixed with 2% Sn of 58.70 kJ/mol, pure aluminium combined with 6% Sn of 16.63 kJ/mol and Aluminium pure mixed with 10% Sn at 47.68 kJ/mol.